The implication of Islamic Boarding School policy in developing the quality of Islamic religious education in East Java, Indonesia - Wiyono, Dwi Fitri (Technium Social Sciences Journal, 2022)
This paper discusses the implication of Islamic boarding school education quality policy in Indonesia. The presence of state in developing quality began with the issuance of Law Number 18 of 2019 concerning Islamic Boarding Schools and Presidential Decree 82 of 2021 concerning funding for implementation of Islamic Boarding Schools which later affected its existence in Indonesia, especially Islamic boarding schools in East Java. The results have implications for 2 aspects, namely the management of macro aspects and micro aspects. Management on macro aspects, among others; first, the regulatory aspect of Islamic Boarding School quality assurance, second, the funding aspect of Islamic Boarding School, and third, the managerial aspect of Islamic Boarding School. While the management of the micro aspects, among others; (1) The philosophical values and vision and mission of Islamic Boarding School; (2) Human resource management; (3) Management of facilities and infrastructure.